Decoding the locational information in the orb web vibrations of Araneus diadematus and Zygiella x-notata. Issue 154 (31st May 2019) - Mortimer, B.; Soler, A.; Wilkins, L.; Vollrath, F.
Abstract : A spider's web is a multifunctional structure that captures prey and provides an information platform that transmits vibrational information. Many physical factors interact to influence web vibration and information content, from vibration source properties and input location, to web physical properties and geometry. The aim of the study was to test whether orb web vibration contains information about the location of the source of vibration. We used finite-element analysis model webs to control and vary major physical factors, investigating webs where spiders use a direct or remote monitoring strategy. When monitoring with eight sensors (legs) at the web centre, a comparison of longitudinal and transverse wave amplitude between the sensors gave sufficient information to determine source direction and distance, respectively. These localization cues were robust to changes in source amplitude, input angle and location, with increased accuracy at lower source amplitudes. When remotely monitoring the web using a single thread connected to the web's hub (a signal thread), we found that locational information was not available when the angle of the source input was unknown. Furthermore, a free sector and a stiff hub were physical mechanisms to aid information transfer, which provides insights for bioinspired fibre networks for sensing technologies.